2003
DOI: 10.1177/004051750307301203
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Spun-Like Textured Yarn Processed with Various Plied Filaments and Different Stages of Emery Wheels

Abstract: A new rotor twister is used to fabricate spun-like filament yarns. The raw material, draw-textured yarn (DTY), becomes as the core yarn and the wrapping yarn. During twisting, the core yarn passes through a pair of emery wheels to make the surface hairy. In this experiment, the rotor speed, twist multiplier, number of emery wheels, and denier of the DTY are varied. The effects of these parameters on tenacity, elongation, and hairiness numbers are examined and discussed. Reducing the number of emery wheels incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(4 reference statements)
2
0
0
Order By: Relevance
“…It is clear from the observation that as the yarn twist increased, the RKM value increased. These results are in line with the findings that the tenacity of yarn increased with the twist multiplier when it did not exceed the optimum twist multiplier (Lei, 2003).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is clear from the observation that as the yarn twist increased, the RKM value increased. These results are in line with the findings that the tenacity of yarn increased with the twist multiplier when it did not exceed the optimum twist multiplier (Lei, 2003).…”
Section: Resultssupporting
confidence: 91%
“…It is clear from the results that the single yarn strength increased with the increase in twist in the yarn. These results are in line with the findings that the tenacity of yarn increased with the twist multiplier when it did not exceed the optimum twist multiplier (Lei, 2003). Similarly, in another study it was found that as the twist level increased, the yarn strength increased up to a certain level, beyond which the increase in twist actually decreased the strength of staple yarn (Palaniswamy and Mohamed, 2006).…”
Section: Resultssupporting
confidence: 86%